ANALISIS KANDUNGAN UNSUR DAN SENYAWA KIMIA PADA IKAN SAPU-SAPU (Pterygoplichthys pardalis) DI DANAU SIDENRENG - Hasrianti Hasrianti; Armayani M; Surianti Surianti; A. Rini Sahni Putri; Damis Damis; Saman Gita Marewa; Abd. Hakim Akbar (EnviroScienteae, 2022)
A Suckermouth catfish is one type of fish that is considered a pest in the waters because it is invasive (invasive species). In addition to being a pest species, Suckermouth catfish is also known as one type of fish species that has a fairly high heavy metal content in some waters that are classified as polluted waters. This research was conducted with the aim of knowing the content of chemical elements contained in Suckermouth catfish. Based on the results of XRF (X-Ray Fluoroscence) analysis, it shows that there are 14 chemical elements found in the organs of the broom fish, including Sulfur (S), Potassium (K), Calcium (Ca), Phosphorus (F), Silicon (Si). ), Chlorine (Cl), Iron (Fe), Zinc (Zn), Niobium (Nb), Molybdenum (Mo), Antimony (Sb), Ruthenium (Ru), Indium (In), Tin (Sn) and Titanium (Ti ). Meanwhile, based on the results of XRD (X-Ray Diffraction) analysis on the scales of the Suckermouth catfish, the micrograph results obtained in the form of an amorphous which is indicated by the presence of a hump on the graph consisting of 10% Cadmium Mercury, 81% Phosphorus and 9% Calcium, while in the bone Suckermouth catfish consists of 40% Calcium Hydride, 59% Akermanite, and 0.96% Cadmium.